American Dreams, American Nightmares Culture and Crisis in Residential Real Estate from the Great Recession to the COVID-19 Pandemic. - Horowitz, Daniel, 1938- (University of North Carolina Press, 2022)
"Two decades punctuated by the financial crisis of the Great Recession and the public health crisis of COVID-19 have powerfully reshaped housing in America. By integrating social, economic, intellectual, and cultural histories, this illuminating work shows how powerful forces have both reflected and catalyzed shifts in the way Americans conceptualize what a house is for, in an era that has laid bare the larger structures and inequities of the economy"--